Effects of Titanium Corrosion Products on In Vivo Biological Response: A Basis for the Understanding of Osseointegration Failures Mechanisms - Biguetti, Claudia Cristina; Cavalla, Franco; Fonseca, Angélica Cristina; Tabanez, Andre Petenucci; Siddiqui, Danyal A.; Wheelis, Sutton E.; Taga, Rumio; Fakhouri, Walid D.; Silva, Renato Menezes; Rodrigues, Danieli C.; Garlet, Gustavo Pompermaier (Frontiers in Materials, 2021)
Corrosion resistance is a key feature of titanium biocompatibility. However, Ti surfaces exposed to critical environments (such as, chronic infection and inflammation) can undergo corrosion processes in vivo, leading to an unfavorable biological response and clinical failure, which remains poorly explored. In this study, we characterized an experimental model to replicate the surface features of Ti corrosion process observed within in vivo failures, and the cellular, tissue and molecular events associated with corroded Ti surface implantation into subcutaneous and bone tissue of C57Bl/6 mice. Prior to in vivo implantation, commercially pure Ti Commercially pure titanium and Ti–6Al–4V alloy (Ti64) specimens were exposed to electrochemical polarization in 30% citric acid, while being polarized at 9 V against a saturated calomel electrode for 20 min. The electrochemical attack induced accelerated corrosion on both Ti-based specimens, producing structural and chemical changes on the surface, comparable to changes observed in failed implants. Then, microscopy and molecular parameters for healing and inflammation were investigated following control and corroded Ti implantation in subcutaneous (cpTi disks) and oral osseointegration (Ti64 screws) models at 3, 7, 14 and 21 days. The host response was comparatively evaluated between control and corroded Ti groups by microCT (bone), histology (H&E, histomorphometry, immunostaining and picrosirius red), and real-time PCR array for inflammatory and healings markers. Corroded cpTi disks and Ti64 screws induced a strong foreign body response (FBR) from 3 to 21 days-post implantation, with unremitting chronic inflammatory reaction lasting up to 21 days in both subcutaneous and osseointegration models. In the subcutaneous model, FBR was accompanied by increased amount of blood vessels and their molecular markers, as well as increased TRAP+ foreign body giant cell count. In the osseointegration model, failures were identified by an osteolytic reaction/bone loss detected by microCT and histological analyses. The corroded devices were associated with a dominant M1-type response, while controls showed transient inflammation, an M2-type response, and suitable healing and osseointegration. In conclusion, corrosion of Ti-based biomaterials induced exacerbated inflammatory response in both connective tissue and bone, linked to the upregulation of fibrosis, pro-inflammatory and osteoclastic markers and resulted in unfavorable healing and osseointegration outcomes.